SUFISTIC DA'WAH IN THE DIGITAL ERA AND THE ERA OF COVID-19 - Siswoyo Aris Munandar (TASÂMUH, 2022)
Sufism has been considered as teaching that contains tuberculosis (superstition, bid'ah and churafat). Socially, Sufism teaches life as an obstacle to the development and progress of the times so it is not surprising that Al-Ghazali is responsible for the backwardness and decline of Muslims. The accusations and criticisms of Sufism are often unfounded. These accusations and criticisms usually come from groups who do not understand Sufism comprehensively and do not see it from the Sufi perspective itself. As its nature and existence are often misunderstood and belittled. Internet technology, the economy of capitalism, the strengthening of the role of the state in people's lives have shifted the practice of kebatinan teachings. Sufi as a practice of life has never been relevant to today's life, the loss of the modern world has indeed covered all aspects of human life, but it will not stop some efforts to interact in spiritual life. Therefore, the author here is very interested in discussing: how is Sufistic da'wah in the digital era? How can the tarekat be able to use technology as a medium of da'wah? This researcher uses a descriptive approach. The descriptive approach can produce data in the form of a description of words either written or spoken form people and behaviors that can be observed by researchers. According to Candra Malik, today's Sufis do not need to always wear a robe, wear a turban, and hide from the public. Therefore, at this time the Sufis can no longer be detected through the way they dress or the ability to use information technology. Therefore, Sufism actors use social media to preach Sufi teachings of Sufism such as Sufi Humor, tasawufonline.com, and Podcasts belonging to TQN practitioner Pontren Suryalaya.